Pagan The Origins of Modern Burma - Aung-Thwin, Michael A. (University of Hawai'i Press, 2018)
Pagan: The Origin of Modern Burma offers major contributions in three areas: the manner in which it integrates original, indigenous source material with social science theory; the significant association it makes between religion and the economy of redistribution; and the model it provides for the rise and decline of a major Buddhist kingdom in Southeast Asia.This is an important book for Southeast Asia scholars and Burma specialists. It will be standard reference work for historians, social scientists, and philologists with an interest in Southeast Asia. Readers interested in general issues of church and state, religion and society, as well as those more specifically concerned with historic and institutional Buddhism will find it a valuable work.